Design, synthesis, characterization, and antimicrobial activity of novel piperazine substituted 1,4-benzoquinones - Yildiz, Mahmut (Elsevier, 2020)
Recently, amine substituted and halogen containing 1,4-benzoquinone molecules have attracted a significant attention because of the efficient biological activities. Thus, novel chlorinated/unchlorinated and piperazine substituted dimethyl-1,4-benzoquinone derivatives (4a-h and 5a-h) were designed, synthesized and characterized in the present paper. Furthermore, antibacterial and antifungal activity performances of the new products were compared and evaluated employing the MIC (Minimum Inhibitory Concentrations) values of reference antimicrobial substances. The compounds of 4a and 4b were highly potent with the MIC values of 4.88 mu g/mL and 78.12 mu g/mL compared to Cefuroxime (MIC = 9.8 mu g/mL against S. epidermidis) and Amikacin (MIC = 128.0 mu g/mL against E. faecalis), respectively. The presence of the chlorine atom in the structure appeared essential, since most of the chlorinated compounds exhibited more improved activity in comparison to those of unchlorinated products. On the other side, an opposite tendency was observed for the antifungal activity that the MIC values of the unchlorinated derivatives were lower in most cases than those of chlorinated ones. According to the obtained results, while chlorinated derivatives, in particular 4a and 4b, can be proposed as potential antibacterial agents with nearly two fold lower MIC values compared to reference drugs, unchlorinated compounds might be suggested as a relatively active antifungal agents which are needed further improvements due to the higher MIC values than those of reference antifungal materials. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: 1,4-Benzoquinone; Piperazine substitution; Structure-activity relationship (SAR); Antibacterial activity; Antifungal activity